Understanding Mobile Payment Continuance in Indonesia: A Brand Equity Perspective Continuance Model - Sarassina, Raden Roro Fosa (Bina Nusantara University, 2022)
As the Indonesian government promotes cashless transactions, more and more efforts are put to make people adopt and keep using electronic money, including mobile payment (m-payment). The research focuses on investigating factors that influence people’s intention to keep using m-payment using two robust theories in the continuance intention: Technology of Acceptance Model (TAM) and Expectation Confirmation Model (ECM). Despite the robustness, the two models do not consider the user’s judgement of the issuer’s brand influence, which is reflected through its brand equity. Then, to fill this gap, A Continuance Model-Brand Equity Perspective (CMBEP) is proposed. The research applies a quantitative approach to validate the model. The data are collected using an online questionnaire to m-payment users. Then, Structural Equation Modelling (SEM) with SmartPLS software test the four hypotheses. Based on the analysis of 420 respondents, it is found that all the hypothesis is supported, and the model is validated. It shows the strongest to weakest relationships: perceived usefulness to satisfaction, perceived ease of use to satisfaction, satisfaction to continuance intention, and brand equity to continuance intention. The findings shed light on m-payment issuers for not only focusing on creating satisfaction for their users but also building a brand with strong equity.